Antibacterial polyester fabric and preparation method thereof
By using chitosan@graphene as the core layer and Ag+ loaded nanofiber as the leather layer in polyester fabric, antibacterial polyester fabric with a leather core structure is prepared through melt spinning technology, which solves the decline in antibacterial performance and mechanics in the prior art. The problem of insufficient performance achieves efficient and long-lasting antibacterial effects and good mechanical properties.
Patent Information
- Application Number
- CN202411354923.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-07
AI Technical Summary
In the long-term use of existing antibacterial polyester fabrics, silver ions are prone to fall off, resulting in a degradation of antibacterial properties. In the blended spinning technology, Ag-TiO2 composite nanoparticles are unevenly dispersed, hindering the full release of antibacterial properties.
Antibacterial polyester fabric with a leather core structure was prepared by melt spinning with chitosan@graphene as the core layer, Ag+ loaded nanofiber, PET, and spinning agent as the cortex, which significantly improved the antibacterial and mechanical properties.
The uniform distribution of antibacterial agents in the material is achieved, which significantly improves the antibacterial and mechanical properties, and meets the needs of long-term use.
Smart Images

Figure BDA0005063338380000101 
Figure BDA0005063338380000111 
Figure BDA0005063338380000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile raw material preparation, and in particular to an antibacterial polyester fabric with a skin-core structure. Background Art
[0002] In recent years, with the improvement of living standards and the enhancement of health awareness, the market demand for antibacterial textiles has continued to grow, especially polyester antibacterial fabrics, which have been valued for their durability and cost-effectiveness. As a synthetic fiber, polyester does not have antibacterial properties by itself, so it needs to be given antibacterial functions through antibacterial finishing technology. Commonly used antibacterial finishing technologies mainly include post-finishing processing and co-spinning. Post-finishing processing technology achieves antibacterial effects by coating antibacterial agents on the surface of fabrics, but antibacterial agents are easy to fall off during the washing process of fabrics, resulting in the reduction of antibacterial effects over time, which is difficult to meet the actual use needs of polyester fabrics. Therefore, it is a challenge to develop antibacterial polyester fabrics with good washability and long-lasting antibacterial effects. Co-spinning technology is to introduce antibacterial materials during the polymerization process, so that they are evenly dispersed and combined in the spinning slices, and the obtained fibers have long-lasting antibacterial properties. Chitosan and graphene oxide are both antibacterial materials. Combining chitosan and graphene, the synergistic effect of the two can not only significantly improve the antibacterial properties, but also improve the mechanical properties of the fabrics. In addition, elemental silver is a broad-spectrum antibacterial agent that can continuously release silver ions and has a long-lasting antibacterial effect. It has good application prospects in the field of antibacterial materials. Domestic patent CN202210268215 discloses a wear-resistant nano-silver antibacterial fabric and its preparation process, which immerses polyester fibers in a nano-silver solution to give the fibers antibacterial properties. Although the fabric obtained by this method has certain antibacterial properties, there is a risk of silver ions falling off during long-term use, resulting in a decrease in antibacterial properties and failure. Domestic patent CN201810411506 discloses a graphene fiber and a preparation method and product. The method uses Ag-TiO 2 Composite nanoparticles and polypropylene chips were used as raw materials to prepare graphene antibacterial fibers by melt spinning. The graphene antibacterial fibers obtained by this method have long-lasting antibacterial properties. 2 The composite nanoparticles are embedded in the graphene fibers, and the Ag-TiO 2 The composite nanoparticles have the disadvantage of uneven dispersion to a certain extent, which hinders the full release of antibacterial properties. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide an antibacterial polyester fabric, which is melt-spinned with chitosan@graphene as the core layer, Ag +The antibacterial polyester fabric with a skin-core structure is prepared by loading nano-short fibers, PET, and spinning aids as the skin layer, which significantly improves the antibacterial and mechanical properties of the polyester fabric and can meet the actual use needs of the antibacterial polyester fabric.
[0004] Technical solution: A method for preparing an antibacterial polyester fabric, characterized in that it comprises the following steps: S1. With chitosan@graphene as the core layer, Ag + Nano-short fibers, PET and spinning aids are loaded as the sheath layer, and a sheath-core composite polyester filament is prepared by melt spinning; S2. The core-sheath structure polyester composite filaments are used as warp yarns and weft yarns respectively, and the resulting fabrics are immersed in a reducing agent after shuttle spinning to obtain antibacterial polyester fabrics. Preferably, the spinning aids in S1 are dispersants and antioxidants, the mass ratio of dispersants to antioxidants is 0.1-0.4:0.04-0.2, the dispersant is one or more of pentaerythritol stearate, polyester micropowder wax and polyacrylic acid, and the antioxidant is one or more of antioxidant 1010, antioxidant 1076 and antioxidant 626. Preferably, Ag in S1 + The loaded nano short fibers are one or more of cotton fibers, hemp fibers and bamboo fibers. Preferably, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. Graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. The chitosan / acetic acid solution was added dropwise to the dispersion and then EDC and DMAP were added to obtain a mixed solution; S1-3. After the mixed solution is fully reacted at a certain temperature under nitrogen protection, it is filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product is added to a mixed solution of phosphoric acid and ethanol to react sufficiently to obtain chitosan@graphene with a particle size of 0.6-1.0 μm. Preferably, Ag in S1 + The preparation of loaded nanofibers comprises the following steps: S2-1. Prepare a certain concentration of AgNO 3 solution, and adding an ammonia solution to adjust the pH of the mixed solution; S2-2. The nanofibers are steam exploded to obtain nanofibers having an aspect ratio of 4 to 7; S2-3. Add the nanofibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was fully adsorbed and soaked to obtain Ag + Loaded nanofibers. Preferably, the melt spinning temperature in S1 is 250-260° C., the mass ratio of the core layer to the skin layer is 0.3-1, and the mass ratio of the polyester melt to the silver-loaded cotton fiber is 6-8:0.2-0.4. Preferably, the reducing agent in S2 is a sodium citrate trisodium solution with a concentration of 5 to 12 g / L, and the immersion time is 10 to 60 min. Preferably, the mass ratio of chitosan, graphene, EDC and DMAP is: 1 to 3: 3 to 5: 1 to 3: 0.3 to 1, the reaction temperature under nitrogen protection is 60 to 80°C, the reaction time is 4 to 8 hours, and the volume ratio of phosphoric acid to ethanol is 0.2 to 0.8. Preferably, the AgNO 3 The concentration of the solution is 5-10 g / L, the pH value of the mixed solution is 6-8, the mass ratio of the nano-short fibers to the silver nitrate solution is 40:1-80:1, and the immersion time is 10-30 minutes. Preferably, the steam explosion is carried out at a temperature of 180 to 240° C., a pressure of 0.69 to 4.83 MPa, and a time of 8 to 18 min. Beneficial effects: The antibacterial polyester fabric of the present invention has the following advantages: 1. In the present invention, chitosan@graphene is used as the core layer, Ag + The nano-short fibers, PET and spinning aids are loaded as the cortex, and a composite polyester filament with a core-skin structure is prepared by melt spinning. The core-skin structure design makes the antibacterial agent more evenly distributed in the material, thereby improving the overall antibacterial performance of the material. 2. In the present invention, thanks to the combined effects of the physical and chemical properties of graphene and the biocompatibility and antibacterial properties of chitosan, chitosan is grafted onto the graphene surface to produce a synergistic effect, which enhances the antibacterial properties while providing better mechanical stability, thus meeting the requirements for long-term use; 3. Ag in the present invention + The loaded nano short fibers form a dendritic silver structure after steam explosion. During melt spinning, the dendritic silver structures interact with each other to form a network-like silver structure. After reduction, a network-like silver single substance structure is formed, which helps to fully exert the antibacterial effect. 4. In the present invention, the skin layer contains an inorganic antibacterial agent and the core layer contains an organic antibacterial agent. The organic antibacterial agent and the inorganic antibacterial agent are combined to achieve a synergistic effect to achieve broad-spectrum antibacterial and long-acting antibacterial effects, significantly improving the antibacterial effect. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 A method for preparing an antibacterial polyester fabric comprises the following steps: S1. With chitosan@graphene as the core layer, Ag + The loaded nano-cotton staple fibers, PET and spinning aids were the skin layer, the mass ratio of the core layer to the skin layer was 0.3, the spinning aids were dispersants (pentaerythritol stearate and polyester micro-powder wax) and antioxidants (antioxidant 1010 and antioxidant 1076), PET, Ag + The mass ratio of loaded nano-cotton staple fibers, dispersant and antioxidant was 6:0.2:0.1:0.04, and composite polyester filaments with a core-skin structure were prepared by melt spinning at 250°C. S2. The core-sheath polyester composite filaments were used as warp yarns and weft yarns respectively, and after shuttle spinning, the resulting fabrics were immersed in 25 g of 5 g / L trisodium citrate solution for 10 min to obtain antibacterial polyester fabrics. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 150 g of a 20 wt % chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 30 g of EDC and 9 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 60°C for 4 h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.2, and then fully reacted to obtain chitosan@graphene with a particle size of 0.6 μm. Among them, Ag in S1 + The preparation of loaded nano-cotton staple fibers comprises the following steps: S2-1. Prepare 5g concentration of 5g / LAgNO 3 solution, and adding ammonia solution to adjust the pH value of the mixed solution to 6; S2-2. 200 g of nano cotton fibers were steam exploded at 180 ° C for 8 min at a pressure of 0.69 MPa to obtain nano cotton staple fibers having an aspect ratio of 4; S2-3. Add the nano cotton staple fibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was heated to 60°C and fully immersed and adsorbed for 10 minutes to obtain Ag + Loaded nanocotton short fibers. Example 2 A method for preparing an antibacterial polyester fabric comprises the following steps: S1. With chitosan@graphene as the core layer, Ag +The loaded nano-cotton staple fibers, PET and spinning aids were the skin layer, the mass ratio of the core layer to the skin layer was 1, the spinning aids were dispersants (pentaerythritol stearate and polyester micro-powder wax) and antioxidants (antioxidant 1010 and antioxidant 1076), PET, Ag + The mass ratio of loaded nano-cotton staple fibers, dispersant and antioxidant was 8:0.4:0.4:0.2, and composite polyester filaments with a core-skin structure were prepared by melt spinning at 260°C. S2. The core-sheath structure polyester composite filaments are used as warp yarns and weft yarns respectively. After shuttle spinning, the resulting fabrics are immersed in 75 g of 12 g / L trisodium citrate solution for 60 min to obtain antibacterial polyester fabrics. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 270 g of a 20 wt% chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 54 g of EDC and 18 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 80°C for 8h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.8, and then fully reacted to obtain chitosan@graphene with a particle size of 1.0 μm. Among them, Ag in S1 + The preparation of loaded nano-cotton staple fibers comprises the following steps: S2-1. Prepare 5g of 10g / LAgNO 3 solution, and adding ammonia solution to adjust the pH value of the mixed solution to 8; S2-2. 400 g of nano cotton fibers were steam exploded at 240 ° C for 18 min under a pressure of 4.83 MPa to obtain nano cotton staple fibers with an aspect ratio of 7; S2-3. Add the nano cotton staple fibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was heated to 90°C and fully immersed and adsorbed for 30 minutes to obtain Ag + Loaded with nano-cotton staple fibers. Example 3 A method for preparing an antibacterial polyester fabric comprises the following steps: S1. With chitosan@graphene as the core layer, Ag + The loaded nano-cotton staple fibers, PET and spinning aids were the skin layer, the mass ratio of the core layer to the skin layer was 0.4, the spinning aids were dispersants (pentaerythritol stearate, polyacrylic acid and polyester micro-powder wax) and antioxidants (antioxidant 1010 and antioxidant 1076), PET, Ag+ The mass ratio of loaded nano-cotton staple fibers, dispersant and antioxidant was 7:0.3:0.2:0.1, and composite polyester filaments with a core-skin structure were prepared by melt spinning at 250°C. S2. The core-sheath structure polyester composite filaments are used as warp yarns and weft yarns respectively. After shuttle spinning, the resulting fabrics are immersed in 50 g of 12 g / L trisodium citrate solution for 20 min to obtain antibacterial polyester fabrics. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 180 g of a 20 wt % chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 40 g of EDC and 12 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 70°C for 5 h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.4 to fully react to obtain 0.8 μm chitosan@graphene. Among them, Ag in S1 + The preparation of loaded nano-cotton staple fibers comprises the following steps: S2-1. Prepare 5g concentration of 5g / LAgNO 3 solution, and adding ammonia solution to adjust the pH value of the mixed solution to 6; S2-2. 300 g of nano cotton fibers were steam exploded at 190 ° C for 8 min at a pressure of 3.22 MPa to obtain nano cotton staple fibers having an aspect ratio of 6; S2-3. Add the nano cotton staple fibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was heated to 70°C and fully immersed and adsorbed for 15 minutes to obtain Ag + Loaded with nano-cotton staple fibers. Example 4 A method for preparing an antibacterial polyester fabric comprises the following steps: S1. With chitosan@graphene as the core layer, Ag + The nano-hemp staple fibers, PET and spinning aids were loaded as the skin layer, the mass ratio of the core layer to the skin layer was 0.4, the spinning aids were dispersants (pentaerythritol stearate, polyester micropowder wax and polyacrylic acid) and antioxidants (antioxidant 1010 and antioxidant 626), PET, Ag + The mass ratio of loaded nano-hemp staple fibers, dispersant and antioxidant was 6:0.2:0.1:0.04, and composite polyester filaments with a core-skin structure were prepared by melt spinning at 255°C. S2. The core-sheath structure polyester composite filaments are used as warp yarn and weft yarn respectively, and after shuttle spinning, the resulting fabric is immersed in 70g of 10g / L trisodium citrate solution for 30min to obtain an antibacterial polyester fabric. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 200 g of a 20 wt% chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 45 g of EDC and 12 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 65°C for 6 h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.5 and then fully reacted to obtain 0.6-μm chitosan@graphene. Among them, Ag in S1 + The preparation of loaded nano-hemp staple fibers comprises the following steps: S2-1. Prepare 5g concentration of 5g / LAgNO 3 solution, and adding ammonia solution to adjust the pH value of the mixed solution to 7; S2-2. 250 g of nano cotton fibers were steam exploded at 200 ° C for 12 min under a pressure of 4.15 MPa to obtain nano hemp staple fibers with an aspect ratio of 6; S2-3. Add the nano cotton staple fibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was heated to 75°C and fully immersed and adsorbed for 15 minutes to obtain Ag + Loaded with nano-hemp staple fibers. Example 5 A method for preparing an antibacterial polyester fabric comprises the following steps: S1. With chitosan@graphene as the core layer, Ag + The loaded nano bamboo staple fibers, PET and spinning aids were the skin layer, the mass ratio of the core layer to the skin layer was 0.7, the spinning aids were dispersants (pentaerythritol stearate and polyester micropowder wax) and antioxidants (antioxidant 1010 and antioxidant 1076), PET, Ag + The mass ratio of loaded nano bamboo staple fibers, dispersant and antioxidant was 7:0.4:0.3:0.1, and composite polyester filaments with a core-skin structure were prepared by melt spinning at 260°C. S2. The core-sheath structure polyester composite filaments are used as warp yarns and weft yarns respectively. After shuttle spinning, the resulting fabrics are immersed in 65 g of 12 g / L trisodium citrate solution for 20 min to obtain antibacterial polyester fabrics. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 160 g of a 20 wt% chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 45 g of EDC and 10 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 70°C for 8h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.5, and then fully reacted to obtain chitosan@graphene with a particle size of 1.0 μm. Among them, Ag in S1 + The preparation of loaded nano bamboo staple fibers comprises the following steps: S2-1. Prepare 5g concentration of 5g / LAgNO 3 solution, and adding ammonia solution to adjust the pH value of the mixed solution to 6; S2-2. 200 g of nano bamboo fiber was steam exploded at 200 ° C for 12 min under a pressure of 3.5 MPa to obtain nano bamboo staple fibers having an aspect ratio of 6; S2-3. Add the nano bamboo short fibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was heated to 75°C and fully immersed and adsorbed for 15 minutes to obtain Ag + Loaded with nano-hemp staple fibers. Example 6 A method for preparing an antibacterial polyester fabric comprises the following steps: S1. With chitosan@graphene as the core layer, Ag + The loaded nano bamboo staple fiber, PET and spinning aids are the skin layer, the mass ratio of the core layer to the skin layer is 0.6, the spinning aids are dispersant (pentaerythritol stearate) and antioxidant (antioxidant 1010), PET, Ag + The mass ratio of loaded nano bamboo staple fibers, dispersant and antioxidant was 6:0.4:0.3:0.1, and composite polyester filaments with a core-skin structure were prepared by melt spinning at 260°C. S2. The core-sheath structure polyester composite filaments were used as warp yarns and weft yarns respectively. After shuttle spinning, the resulting fabrics were immersed in 40 g of 10 g / L trisodium citrate solution for 30 min to obtain an antibacterial polyester fabric with a warp density to weft density ratio of 1.5. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 180 g of a 20 wt% chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 50 g of EDC and 12 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 75°C for 6 h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.6 to fully react to obtain chitosan@graphene with a particle size of 0.8 μm. Among them, Ag in S1 + The preparation of loaded nano bamboo staple fibers comprises the following steps: S2-1. Prepare 8g of 5g / LAgNO 3 solution, and adding ammonia solution to adjust the pH value of the mixed solution to 6; S2-2. 480 g of nano bamboo staple fibers were steam exploded at 200 ° C for 14 min under a pressure of 3.25 MPa to obtain nano bamboo staple fibers having an aspect ratio of 6; S2-3. Add the nano bamboo short fibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was heated to 80°C and fully immersed and adsorbed for 18 minutes to obtain Ag + Loaded with nano-hemp staple fibers. Example 7 A method for preparing an antibacterial polyester fabric comprises the following steps: S1. With chitosan@graphene as the core layer, Ag + The loaded nano-cotton staple fibers, PET and spinning aids were the skin layer, the mass ratio of the core layer to the skin layer was 0.7, the spinning aids were dispersants (pentaerythritol stearate and polyester micro-powder wax) and antioxidants (antioxidant 1010 and antioxidant 1076), PET, Ag + The mass ratio of loaded nano-cotton staple fibers, dispersant and antioxidant was 6:0.2:0.1:0.04, and composite polyester filaments with a core-skin structure were prepared by melt spinning at 250°C. S2. The core-sheath structure polyester composite filaments are used as warp yarn and weft yarn respectively. After shuttle spinning, the resulting fabric is immersed in 50 g of 10 g / L trisodium citrate solution for 20 minutes to obtain an antibacterial polyester fabric. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 160 g of a 20 wt% chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 30 g of EDC and 9 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 60°C for 8h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.2 to fully react to obtain chitosan@graphene with a particle size of 0.8 μm. Among them, Ag in S1 + The preparation of loaded nano-cotton staple fibers comprises the following steps: S2-1. Prepare 5g concentration of 5g / LAgNO 3 solution, and adding ammonia solution to adjust the pH value of the mixed solution to 6; S2-2. 200 g of nano cotton staple fibers were steam exploded at 200 ° C for 16 min under a pressure of 3.25 MPa to obtain nano bamboo staple fibers having an aspect ratio of 6; S2-3. Add the nano bamboo short fibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was heated to 80°C and fully immersed and adsorbed for 18 minutes to obtain Ag + Loaded with nano-cotton staple fibers. Comparative Example 1 The difference between Comparative Example 1 and Example 7 is that the graphene is not graft-modified. A method for preparing an antibacterial polyester fabric comprises the following steps: S1. With graphene as the core layer, Ag + The loaded nano-cotton staple fibers, PET and spinning aids were the skin layer, the mass ratio of the core layer to the skin layer was 0.7, the spinning aids were dispersants (pentaerythritol stearate and polyester micro-powder wax) and antioxidants (antioxidant 1010 and antioxidant 1076), PET, Ag + The mass ratio of loaded nano-cotton staple fibers, dispersant and antioxidant was 6:0.2:0.1:0.04, and composite polyester filaments with a core-skin structure were prepared by melt spinning at 250°C. S2. The core-sheath structure polyester composite filaments are used as warp yarn and weft yarn respectively. After shuttle spinning, the resulting fabric is immersed in 50 g of 10 g / L trisodium citrate solution for 20 minutes to obtain an antibacterial polyester fabric. Among them, Ag in S1 + The preparation of loaded nano-cotton staple fibers comprises the following steps: S2-1. Prepare 5g concentration of 5g / LAgNO 3 solution, and adding ammonia solution to adjust the pH value of the mixed solution to 6; S2-2. 200 g of nano bamboo staple fibers were steam exploded at 200 ° C for 16 min under a pressure of 3.25 MPa to obtain nano bamboo staple fibers having an aspect ratio of 6; S2-3. Add the nano bamboo short fibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was heated to 80°C and fully immersed and adsorbed for 18 minutes to obtain Ag + Loaded with nano-cotton staple fibers. Comparative Example 2 The difference between Comparative Example 2 and Example 7 is that no Ag is adsorbed on the nano cotton staple fibers. + . A method for preparing an antibacterial polyester fabric comprises the following steps: S1. Chitosan@graphene was used as the core layer, nano cotton staple fiber, PET and spinning aids were used as the skin layer, the mass ratio of the core layer to the skin layer was 0.7, the spinning aids were dispersants (pentaerythritol stearate and polyester micropowder wax) and antioxidants (antioxidant 1010 and antioxidant 1076), the mass ratio of PET, nano cotton staple fiber, dispersant and antioxidant was 6:0.2:0.1:0.04, and a composite polyester filament with a core-skin structure was prepared by melt spinning at 250°C; S2. The core-sheath structure polyester composite filaments are used as warp yarn and weft yarn respectively. After shuttle spinning, the resulting fabric is immersed in 50 g of 10 g / L trisodium citrate solution for 20 minutes to obtain an antibacterial polyester fabric. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 160 g of a 20 wt% chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 30 g of EDC and 9 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 60°C for 8h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.2 to fully react to obtain chitosan@graphene with a particle size of 0.8 μm. The preparation of the nano-cotton staple fibers in S1 comprises the following steps: 200 g of the nano-cotton staple fibers are steam exploded at 200° C. for 16 min under a pressure of 3.25 MPa to obtain nano-cotton staple fibers with an aspect ratio of 6. Comparative Example 3 The difference between Comparative Example 3 and Example 7 is that Ag + The loaded nano-cotton staple fibers were prepared by low-speed pulverization. A method for preparing an antibacterial polyester fabric comprises the following steps: S1. With chitosan@graphene as the core layer, Ag +The loaded nano-cotton staple fibers, PET and spinning aids were the skin layer, the mass ratio of the core layer to the skin layer was 0.7, the spinning aids were dispersants (pentaerythritol stearate and polyester micro-powder wax) and antioxidants (antioxidant 1010 and antioxidant 1076), PET, Ag + The mass ratio of loaded nano-cotton staple fibers, dispersant and antioxidant was 6:0.2:0.1:0.04, and composite polyester filaments with a core-skin structure were prepared by melt spinning at 250°C. S2. The core-sheath structure polyester composite filaments are used as warp yarn and weft yarn respectively. After shuttle spinning, the resulting fabric is immersed in 50 g of 10 g / L trisodium citrate solution for 20 minutes to obtain an antibacterial polyester fabric. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 160 g of a 20 wt% chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 30 g of EDC and 9 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 60°C for 8h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.2 to fully react to obtain chitosan@graphene with a particle size of 0.8 μm. Among them, Ag in S1 + The preparation of loaded nano-cotton staple fibers comprises the following steps: S2-1. Prepare 5g concentration of 5g / LAgNO 3 solution, and adding ammonia solution to adjust the pH value of the mixed solution to 6; S2-2. 200g of nano-cotton staple fibers were crushed with a wall-breaking machine and crushed at 1000rpm for 10s to obtain nano-cotton staple fibers having an aspect ratio of 6; S2-3. Add the nano bamboo short fibers prepared in step S2-2 to the AgNO prepared in step S2-1. 3 The solution was heated to 80°C and fully immersed and adsorbed for 18 minutes to obtain Ag + Loaded with nano-cotton staple fibers. Comparative Example 4 The difference between Comparative Example 4 and Example 7 is that nanosilver particles are directly added into the skin layer for spinning. A method for preparing an antibacterial polyester fabric comprises the following steps: S1. Chitosan@graphene was used as the core layer, nanosilver particles, PET and spinning aids were used as the skin layer, the mass ratio of the core layer to the skin layer was 0.7, the spinning aids were dispersants (pentaerythritol stearate and polyester micropowder wax) and antioxidants (antioxidant 1010 and antioxidant 1076), the mass ratio of PET, nanosilver particles, dispersants and antioxidants was 6:0.2:0.1:0.04, and a composite polyester filament with a skin-core structure was prepared by melt spinning at 250°C; S2. The core-sheath structure polyester composite filaments are used as warp yarn and weft yarn respectively. After shuttle spinning, the resulting fabric is immersed in 50 g of 10 g / L trisodium citrate solution for 20 minutes to obtain an antibacterial polyester fabric. Wherein, the preparation of chitosan@graphene in S1 comprises the following steps: S1-1. 90 g of graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. 160 g of a 20 wt% chitosan / acetic acid solution was added dropwise to the dispersion, followed by addition of 30 g of EDC and 9 g of DMAP to obtain a mixed solution; S1-3. The mixed solution was reacted at 60°C for 8h under nitrogen protection, and then filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product was added into a mixed solution of phosphoric acid and ethanol in a volume ratio of 0.2 to fully react to obtain chitosan@graphene with a particle size of 0.8 μm. Comparative Example 5 The difference between Comparative Example 5 and Example 7 is that only PET is used for spinning. Performance Testing The antibacterial properties of the samples prepared in Examples 1-7 of the present invention and Comparative Examples 1-5 were tested, and the results are shown in Table 1. Table 1 Antibacterial and washing resistance properties of different samples Note: 1. Since polyester fiber itself does not have antibacterial properties, no antibacterial test was performed on Comparative Example 5; 2. Refer to GB / T 20944.3-2008 standard on fabric antibacterial test method. The antibacterial properties of silver-loaded cotton fabric were tested by oscillation method. Gram-negative E. coli (ATCC 25922) and Gram-positive S. aureus (CMCC26003) were selected as test strains. Before each test, the samples, glassware, nutrient broth and nutrient agar used in the test were sterilized in a 121℃, 103kpa autoclave for 30min for use. A small amount of bacteria was taken in 20mL nutrient broth and placed in a 37℃ constant temperature oscillator at 130r / min for 18-20h, and then the cultured bacterial solution was diluted to 3-5×105CFU / mL using nutrient broth and 0.03mol / LPBS (phosphate buffer, PH=7.0~7.2) respectively. Take 3mL of the diluted bacterial solution and 0.1g of sample and culture them in a 37℃ constant temperature oscillator at 130r / min for 24h. After 15 mL of nutrient agar was poured into the culture dish and cooled and solidified, 100 μL of the bacterial solution cultured with the sample was diluted serially (×101, ×102, ×103, ×104) with 0.03 mol / L phosphate buffer and transferred to the nutrient agar. The culture was carried out in a 37°C biochemical incubator for 24 hours. The antibacterial rate was calculated as follows: Where: Y is the antibacterial rate (%); Wb is the number of colonies of the control sample after 18 hours of culture; Wc is the number of colonies of the antibacterial fabric after 18 hours of culture; 3. Refer to the test method for textile washing fastness in GB / T12490-2014 standard, cut the antibacterial polyester fabric into 10cm×10cm. Prepare 4g / L soap solution, bath ratio 1:50, select A1S, time 0.5h, temperature 40℃, soap washing once is equivalent to 5 machine washings, put the soap solution and 10 steel balls into the washing cup of the washing fastness instrument, wait for preheating to complete, and then put the fabric to be washed. After washing, rinse the fabric with deionized water, dry it at 60℃, and then test the antibacterial properties of the fabric. The tear strength test was performed on the samples prepared in Examples 1-7 of the present invention and Comparative Examples 1-5. The results are shown in Table 2. Table 2 Tear strength of different samples Note: 1. Refer to GB / T 3917.2-2009 standard on the test method of single seam tear strength of fabrics. Cut into long fabric samples with a width of 50mm and a length of 220mm, cut a 100mm long crack along the length direction at 1 / 2 of the width of the long fabric sample, and test each piece of fabric 3 times in the warp and weft directions to take the average value. 2. The breaking strength of fabrics is affected by many factors, such as yarn strength and friction resistance between fibers. It can be seen from Examples 1 to 7 and Comparative Examples 1 to 5 that the antibacterial polyester fabric with a skin-core structure prepared in the present invention, which has chitosan @ graphene as the core layer and nano-silver particles, PET and spinning aids as the skin layer, has good mechanical properties. Compared with Comparative Example 5, Example 7 has a warp tear strength increased by 43.02% and a weft tear strength increased by 25.01%. The improvement in the mechanical properties of antibacterial polyester fabrics is due to the high strength and high modulus of graphene itself, and on the other hand, it is due to the high strength and high modulus of Ag. + The loaded nanofibers are randomly distributed in the cortex, reducing stress concentration. Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing an antibacterial polyester fabric, characterized in that: The following steps are involved: S1. With chitosan@graphene as the core layer, Ag + Nano-short fibers, PET and spinning aids are loaded as the sheath layer, and a sheath-core composite polyester filament is prepared by melt spinning; S2. The core-sheath polyester composite filaments are used as warp yarns and weft yarns respectively, and the resulting fabrics are immersed in a reducing agent after shuttle spinning to obtain antibacterial polyester fabrics.
2. The method for preparing the antibacterial polyester fabric according to claim 1, characterized in that: The spinning aid in S1 is a dispersant and an antioxidant, the mass ratio of the dispersant to the antioxidant is 0.1-0.4:0.04-0.2, the dispersant is one or more of pentaerythritol stearate, polyester micropowder wax and polyacrylic acid, and the antioxidant is one or more of antioxidant 1010, antioxidant 1076 and antioxidant 626.
3. The method for preparing the antibacterial polyester fabric according to claim 1, characterized in that: The S1 Ag + The loaded nano short fibers are one or more of cotton fibers, hemp fibers and bamboo fibers.
4. The method for preparing the antibacterial polyester fabric according to claim 1, characterized in that: The preparation of chitosan@graphene in S1 comprises the following steps: S1-1. Graphene was added to DMF and ultrasonicated to obtain a dispersion; S1-2. The chitosan / acetic acid solution was added dropwise to the dispersion and then EDC and DMAP were added to obtain a mixed solution; S1-3. After the mixed solution is fully reacted at a certain temperature under nitrogen protection, it is filtered, washed and dried to obtain an intermediate product; S1-4. The intermediate product is added to a mixed solution of phosphoric acid and ethanol to fully react to obtain chitosan@graphene with a particle size of 0.6-1.0 μm.
5. The method for preparing an antibacterial polyester fabric according to claim 1, characterized in that: The S1 Ag + The preparation of loaded nanofibers comprises the following steps: S2-1 configure a certain concentration of AgNO3 solution, and add an ammonia solution to adjust the pH of the mixed solution; S2-2. The nano-staple fibers are steam exploded to obtain nano-staple fibers having an aspect ratio of 4 to 7, and added to the mixture; S2-3. Add the nanofibers prepared in step S2-2 to the AgNO3 solution prepared in step S2-1, and fully absorb and soak to obtain Ag + Loaded nanofibers.
6. The method for preparing an antibacterial polyester fabric according to claim 1, characterized in that: The temperature of melt spinning in S1 is 250-260° C., the mass ratio of the core layer to the skin layer is 0.3-1, and the mass ratio of the polyester melt to the silver-loaded cotton fiber is 6-8:0.2-0.
4.
7. The antibacterial polyester fabric according to claim 1, characterized in that: The reducing agent in S2 is a trisodium citrate solution with a concentration of 5 to 12 g / L, and the immersion time is 10 to 60 minutes.
8. The method for preparing the antibacterial polyester fabric according to claim 4, characterized in that: The mass ratio of chitosan, graphene, EDC and DMAP is 1-3: 3-5: 1-3: 0.3-1, the reaction temperature under nitrogen protection is 60-80° C., the reaction time is 4-8 hours, and the volume ratio of phosphoric acid to ethanol is 0.2-0.
8.
9. The method for preparing an antibacterial polyester fabric according to claim 5, characterized in that: The concentration of the AgNO3 solution is 5-10 g / L, the pH of the mixed solution is 6-8, the mass ratio of the nano-short fibers to the silver nitrate solution is 40:1-80:1, the heating temperature is 60-90° C., and the immersion time is 10-30 min.
10. The method for preparing an antibacterial polyester fabric according to claim 5, characterized in that: The steam explosion has a temperature of 180-240° C., a pressure of 0.69-4.83 MPa, and a time of 8-18 minutes.
Citation Information
Patent Citations
Graphene fibers, preparation methods and products
CN108588883B
Nano-silver antibacterial fabric with good wear resistance and preparation process thereof
CN114619723A
Cited By
Preparation process of graphene reinforced porous hollow polyester fiber
CN121228393A